Knee injuries: correlation of MRI with arthroscopic findings - Gyawali, Bidur; Joshi, Amit; Kayastha, Nirab (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Knee injuries are common among active adults. Achieving a correct clinical diagnosis is often difficult in acute presentations. Knee arthroscopy is considered the gold standard in diagnosing post-traumatic intra-articular lesions, but it is an invasive procedure requiring a certain degree of expertise. Magnetic Resonance Imaging (MRI) is a non-invasive, sensitive diagnostic tool for knee injuries. This study aims to correlate the findings of MRI with arthroscopy of the knee.Method: This Prospective Observational Study was done at Shree Birendra Hospital, Kathmandu, Nepal from 13 Feb 2016 to 13 Jun 2016. The sensitivity, specificity, and accuracy of MRI findings in ligamentous, meniscal, and osteochondral injuries of the knee were analyzed using arthroscopic findings as standard.Result: Fifty-two patients (35 male and 17 female), mean age 35.4 years were included in the study. The accuracy of MRI for anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), medial meniscus, lateral meniscus, and chondral lesions of the knee were 94%, 100%, 92%,86%, and 86% respectively.Conclusion: The MRI is accurate  (86-94%) in diagnosing Meniscal and Ligamentous injuries of the knee. It has poor sensitivity (22%) for chondral lesions.